Gender, canon and literary history : the changing place of nineteenth-century German women writers - Whittle, Ruth (De Gruyter, 2013)
Gender, Canon and Literary History investigates the reception of 19th-century women's writing in German literary histories by way of case studies. It fills a longstanding gap both in the study of gender and literary history. The case studies concentrate on the reception of women writing in the Age of Romanticism (e.g., Rahel Varnhagen) as well as women who were inspired to write by the German Revolution (e.g., Fanny Lewald).